2018
DOI: 10.1080/10942912.2018.1489841
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, rheological, morphological, and in vitro digestibility properties of cross-linked starch from pearl millet cultivars

Abstract: The effect of epichlorohydrin (0.5%) as a cross-linking agent on physicochemical, rheological, morphological, and in vitro digestion properties of pearl millet starches from different cultivars was studied. Degree of crosslinking (DC) ranged between 40.61% and 89.75%, lower values of DC were observed for cv.HC-10 and cv.HHB-67 whereas higher values were observed for cv.HHB-223 and cv.GHB-732. Cross-linked starch from cv.GHB-732 showed the lowest amylose content, swelling power, and solubility as compared to ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 38 publications
5
12
0
Order By: Relevance
“…The breakdown viscosity was calculated as the difference between the maximum and minimum viscosity and was determined at 54.5 mPaÁs. These results are in agreement with the study of Siroha and Sandhu (2018), who have reported, that breakdown viscosity (BV) of modified starches from millet in the range of 15 to 470 mPaÁs. The final viscosity of the investigated millet paste was 107 mPaÁs, which was determined at the end of the cooling phase.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The breakdown viscosity was calculated as the difference between the maximum and minimum viscosity and was determined at 54.5 mPaÁs. These results are in agreement with the study of Siroha and Sandhu (2018), who have reported, that breakdown viscosity (BV) of modified starches from millet in the range of 15 to 470 mPaÁs. The final viscosity of the investigated millet paste was 107 mPaÁs, which was determined at the end of the cooling phase.…”
Section: Resultssupporting
confidence: 93%
“…In our study, the millet porridges reached the maximum viscosity of 608 mPaÁs at a temperature of 93 °C. This finding is in accordance with the results of Siroha and Sandhu (2018), who found peak viscosities of modified starch from pearl millet cultivars at 299-1164 mPaÁs at 87.4-90.7 °C. Smanalieva et al (2015) reported that the peak viscosity of Kyrgyz variety rice flour using rotational rheometry was determined at 107-372 mPaÁs between 91.4-95.2 °C.…”
Section: Resultssupporting
confidence: 93%
“…We noticed gel like behavior of millet samples that changed between elastic to viscous. Similar observation in pearl millet starch was documented in a study by Siroha and Sandhu (2018).…”
Section: Rheological Measurementssupporting
confidence: 90%
“…CL starches showed rough surfaces and small cavities on the surface of granules. Cross-linking modification slightly affects the starch granule as compared to native starch [36,37]. Native pearl millet starches were polygonal in shape and had well defined edges, while a slightly rough surface and a black zone on the surface were observed for CL starches [37].…”
Section: Morphological Propertiesmentioning
confidence: 96%
“…Cross-linking modification slightly affects the starch granule as compared to native starch [36,37]. Native pearl millet starches were polygonal in shape and had well defined edges, while a slightly rough surface and a black zone on the surface were observed for CL starches [37]. Mirmoghtadaie et al [38] reported that oat starch granules were not affected by cross-linking modification.…”
Section: Morphological Propertiesmentioning
confidence: 99%